2022
DOI: 10.1002/essoar.10512774.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The flocculation state of mud in the lowermost freshwater reaches of the Mississippi River: spatial distribution of sizes, seasonal changes, and their impact on vertical concentration profiles

Abstract: We use in situ measurements of suspended mud to assess the flocculation state of the lowermost freshwater reaches of the Mississippi River. The goal of the study was to assess the flocculation state of the mud in the absence of seawater, the spatial distribution of floc sizes within the river, and to look for seasonal differences between summer and winter. The data was also used to examine whether measured floc sizes could explain observed vertical distributions of suspended sediment concentration through a Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…In the regions of the study area without deposition of mud on the bed, our observed median floc sizes were approximately 100 μm. This is consistent with the range of back‐calculated and observed floc sizes in previous studies of flocs in a variety of other freshwater environments and laboratory conditions (Abolfazli & Strom, 2023; Lamb et al., 2020; Lawrence et al., 2022; Nghiem et al., 2022; Osborn et al., 2023; Soulsby et al., 2013; Zeichner et al., 2021). We find that, despite the range of floc sizes observed in the field between stations, the D 50 of the floc constituent particles remained constant at approximately 14 μm.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the regions of the study area without deposition of mud on the bed, our observed median floc sizes were approximately 100 μm. This is consistent with the range of back‐calculated and observed floc sizes in previous studies of flocs in a variety of other freshwater environments and laboratory conditions (Abolfazli & Strom, 2023; Lamb et al., 2020; Lawrence et al., 2022; Nghiem et al., 2022; Osborn et al., 2023; Soulsby et al., 2013; Zeichner et al., 2021). We find that, despite the range of floc sizes observed in the field between stations, the D 50 of the floc constituent particles remained constant at approximately 14 μm.…”
Section: Discussionsupporting
confidence: 89%
“…Flocs observed in natural environments typically range in diameter from 50–5,000 μm, while flocs processed in laboratory settings typically range between 30 and 800 μm. In both cases, the flocculation process has been empirically and theoretically demonstrated to increase the rate at which aggregates are able to settle out from suspension in the water column, and thus induce the deposition of fine‐grained, cohesive sediment (Abolfazli & Strom, 2022, 2023; Adachi & Tanaka, 1997; Alldredge & Gotschalk, 1988; Bungartz & Wanner, 2004; Curran et al., 2007; Droppo et al., 2000; Dyer, 1989; Dyer et al., 1996; Fennessy et al., 1994; Fox et al., 2004; Gibbs, 1985; Graham & Manning, 2007; Gratiot et al., 2005; Gratiot & Manning, 2004; Huang, 1994; Krone, 1986; Kumar et al., 2010; Lamb et al., 2020; Lick et al., 1992, 1993; A. J. Manning & Bass, 2006; A. Manning & Dyer, 1999; Mikkelsen et al., 2007; Nghiem et al., 2022; Osborn et al., 2021, 2023; Soulsby et al., 2013; Sternberg et al., 1996; Strom & Keyvani, 2011; Syvitski et al., 1995; Van der Lee, 2000; Winterwerp et al., 2006; Zeichner et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the trapping of silt particles within flocs can have an important impact on floc density, and thus on the settling velocity which may increase by more than 50% (Tran & Strom, 2017; Xu et al., 2022). These results were confirmed by river studies (Osborn et al., 2023) and agree with Droppo and Ongley (1994), indicating that salinity is not a needed for sediments to flocculate. Therefore, it can be assumed that the flocs generated in the Rhône River interflow shear layer are a mixture of clays and silts.…”
Section: Discussionsupporting
confidence: 81%
“…Flocculation is well documented in fluvial (e.g., de Boer et al., 2000; Droppo & Ongley, 1992; Osborn et al., 2023; Slattery & Burt, 1997), estuarine (e.g., Gratiot et al., 2017; Verney et al., 2009; Winterwerp, 2002) and marine environments (e.g., Franck, 1973; Li et al., 2004; Many et al., 2016) mainly under steady flow conditions. Flocculation, however, has rarely been investigated in lakes.…”
Section: Introductionmentioning
confidence: 99%
“…(2022) and Osborn et al. (2023) found that turbulence and ionic strength of the ambient water impact the flocculation of mud. Krahl et al.…”
Section: Discussionmentioning
confidence: 99%